Parole practises in Lithuania: Factors predicting court decisions - Jarutiene, Liubove (European journal of probation, 2021)
This article examines factors that predict parole decisions in Lithuanian courts. The study state has a two-stage discretionary parole system where applicants are first evaluated through a parole board hearing, and the board’s decision is then reviewed in court. The study sample included 360 court verdicts from various court institutions. Intergroup comparisons suggest that parole boards tend to grant parole more often than courts. The results of regression analysis suggest that courts weigh heavily on the decision made by the parole board as well as the number of misconduct reports, time left to serve and previous parole or probation violations.